BIIB021: A novel inhibitor to heat shock protein 90–addicted oncology - Liang Yan; Weiming Zhang; Beibei Zhang; Chao Xuan; Daogang Wang (Tumor Biology)
Heat shock protein 90 is induced in response to the cell stress. Its overexpression has been reported in many cancers with poor prognosis. It acts as a chaperone to the client proteins, especially the activated oncoproteins in malignancies to protect them from degradation. Heat shock protein 90 inhibition represented anti-cancer effects in many studies. Previous natural product–based compounds are limited by their association with target toxicities. BIIB021 is an orally available, fully synthetic novel small-molecule heat shock protein 90 inhibitor that has shown strong antitumor activities in a large number of preclinical models and is now under clinical investigation. This review will summarize its therapeutic effects and highlight the prospect of targeting heat shock protein 90 in the cancer therapy.